Distribution and association of interpregnancy weight change with subsequent pregnancy outcomes in Asian women - Ku, Chee Wai (2023)
The extent of interpregnancy weight change and its association with subsequent pregnancy outcomes among Asians remain unclear. We examined changes in maternal body mass index (BMI) between the first two deliveries and outcomes in the second delivery. Medical records of women with their first two consecutive deliveries between 2015 and 2020 at KK Women's and Children's Hospital, Singapore were retrieved. Gestational-age-adjusted BMI was determined by standardising to 12 weeks gestation and interpregnancy BMI change was calculated as the difference between both pregnancies. Pregnancy outcomes were analysed using modified Poisson regression models. Of 6264 included women with a median interpregnancy interval of 1.44 years, 40.7% had a stable BMI change within ± 1 kg/m2, 10.3% lost > 1 kg/m2, 34.3% gained 1-3 kg/m2 and 14.8% gained ≥ 3 kg/m2. Compared to women with stable BMI change, those with > 1 kg/m2 loss had higher risk of low birthweight (adjusted risk ratio [RR] 1.36; 95% confidence interval 1.02-1.80), while those with 1-3 kg/m2 gain had higher risks of large-for-gestational-age birth (1.16; 1.03-1.31), gestational diabetes (1.25; 1.06-1.49) and emergency Caesarean delivery (1.16; 1.03-1.31); these risks were higher in those with ≥ 3 kg/m2 gain. Our study strengthens the case for interpregnancy weight management to improve subsequent pregnancy outcomes.